2023
DOI: 10.3892/etm.2023.11864
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‑152‑5p/ARHGAP6/ROCK axis regulates apoptosis and fibrosis in cardiomyocytes

Abstract: Acute myocardial infarction (AMI) is a fatal cardiovascular disease with a high mortality rate. The discovery of effective biomarkers is crucial for the diagnosis and treatment of AMI. In the present study, miRNA sequencing and reverse transcription-quantitative polymerase chain reaction techniques revealed that the expression of exosome derived miR-152-5p was significantly downregulated in patients with AMI compared with healthy controls. A series of functional validation experiments were then performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Comprehensive analysis indicates that effective intervention could be achieved by suppressing the activation of pro-apoptotic activator in acute myocardial infarction, a grave condition. Nevertheless, the exact mechanism of pro-apoptotic activator's contribution to the evolution of acute myocardial infarction remains incompletely elucidated [33]. Magnetic resonance imaging (MRI) ndings indicated that elevated BCL2L11 molecular levels were intimately linked to the onset of acute myocardial infarction, indicating a de nitive causal association [34].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive analysis indicates that effective intervention could be achieved by suppressing the activation of pro-apoptotic activator in acute myocardial infarction, a grave condition. Nevertheless, the exact mechanism of pro-apoptotic activator's contribution to the evolution of acute myocardial infarction remains incompletely elucidated [33]. Magnetic resonance imaging (MRI) ndings indicated that elevated BCL2L11 molecular levels were intimately linked to the onset of acute myocardial infarction, indicating a de nitive causal association [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is a type of disease involving the heart and blood vessels that is high fatality rate and difficult to treat. , Cardiomyocytes, vascular cells, and fibroblasts release exosomes in the heart with low immunogenicity, and cardiac exosomal miRNAs are able to regulate the expression of sarcomeric genes, antifibrotic activity, and angiogenesis. The modification of natural exosomes into engineered exosomes by bioengineering technology can not only optimize its various biological functions, but also compensate for the weak targeting ability and low drug loading efficiency of natural exosomes. It has been shown that genetic modification of engineered exosomes loaded with miR-425 and miR-744 can target the TGF-β pathway to inhibit angiotensin-induced collagen and fibrin synthesis as a way to inhibit myocardial remodeling .…”
Section: Application Of Engineered Exosomesmentioning
confidence: 99%